2012
DOI: 10.1590/s0006-87052012005000031
|View full text |Cite
|
Sign up to set email alerts
|

Resistência de genótipos de feijoeiro a Bemisia tabaci biótipo B

Abstract: O estudo de genótipos de feijoeiro resistentes à mosca-branca Bemisia tabaci (Genn.) biótipo B (Hemiptera: Aleyrodidae) é de grande importância devido aos danos ocasionados por essa praga à cultura. Neste trabalho, foram estudados a atratividade para adultos, a preferência para oviposição em testes com e sem chance de escolha, o ciclo ovo-adulto e o tipo e número de tricomas presentes nos folíolos. Os experimentos foram realizados em casa de vegetação avaliando-se, inicialmente, cem genótipos de feijoeiro. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
6
0
3
Order By: Relevance
“…In general, insects attempting to colonize plants with antibiosis resistance, that is, plants with the capacity to affect their biology, present reductions in size and weight, diverse deformities, and prolongations in the lifecycle phases and, consequently, high mortality rates (Painter 1951). In the present study, the incubation period of the whitefly eggs in some of the evaluated genotypes was observed; in similar studies, the incubation period of the eggs of B. tabaci biotype B in bean genotypes ranged from 8.00 to 11.00 days (Torres et al 2012;Peixoto and Boiça Júnior 2014). In the present study, the Tybatã and Pérola genotypes had the shortest incubation periods (8.40 and 8.66 days, respectively), consistent with the study by Peixoto and Boiça Júnior (2014), who observed that the incubation periods for these two genotypes ranged from 8.03 to 8.59 days.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In general, insects attempting to colonize plants with antibiosis resistance, that is, plants with the capacity to affect their biology, present reductions in size and weight, diverse deformities, and prolongations in the lifecycle phases and, consequently, high mortality rates (Painter 1951). In the present study, the incubation period of the whitefly eggs in some of the evaluated genotypes was observed; in similar studies, the incubation period of the eggs of B. tabaci biotype B in bean genotypes ranged from 8.00 to 11.00 days (Torres et al 2012;Peixoto and Boiça Júnior 2014). In the present study, the Tybatã and Pérola genotypes had the shortest incubation periods (8.40 and 8.66 days, respectively), consistent with the study by Peixoto and Boiça Júnior (2014), who observed that the incubation periods for these two genotypes ranged from 8.03 to 8.59 days.…”
Section: Discussionsupporting
confidence: 63%
“…This may be due to a lower nutritional adequacy or the presence of antibiotic factors in this genotype, which are aspects that must be better investigated in future studies. Based on the available literature, the duration of the egg to adult period varies between bean genotypes, and there are reports of periods between 16.20 and 41.00 days (Oriani and Lara 2000;Torres et al 2012). Some references reported a large variation in the development period of the whitefly on cowpea genotypes (Cruz et al 2014), cabbage (Villas Bôas et al 1997), cotton (Prado et al 2015), soybean (Cruz and Baldin 2016), tomato (Baldin et al 2005), squash varieties (Baldin and Benduzzi 2010), melon (Baldin et al 2012) and, more recently, peppers, where a duration of 30.25 days was observed (Pantoja et al 2018), similar to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo realizado por Torres et al (2012), os genótipos ARC-3, IAC-Alvorada e Canário 101 podem ter apresentado o tipo de resistência por não preferência para alimentação e/ou antibiose, já que o primeiro acarretou 100% de mortalidade dos imaturos, não diferindo das médias obtidas para os dois últimos, que propiciaram a emergência de apenas 3,3% de adultos.…”
Section: Introductionunclassified
“…Despite the plethora of cashew clones that are commercially available in Brazil, little is known about their resistance to CW and respective mechanisms of resistance. Identification of cashew genotypes expressing traits associated with insect resistance could be valuable for breeding and IPM programs …”
Section: Introductionmentioning
confidence: 99%